Full Lawsuit (Compensation Claim) Its Concept - Its Characteristics - Distinguishing It From The Cancellation Lawsuit - Salhab, Kinda Faisal (Latakia University Journal - Economic and Legal Sciences Series, 2019)
The administrative judiciary contributes to an extremely important role in the field of monitoring the legality of administrative work and protecting the rights and freedoms of individuals, and this is through its separation in the cases brought before it. It also imposes the rule of law on individuals, which ultimately leads to the establishment of a state of law, a state of institutions, and a state of rights and freedoms. These concepts cannot be enshrined in the ground without a role for the administrative judiciary. Administrative courts exercise their control through two types of lawsuits, namely the lawsuit for cancellation and the case for a full court. The cancellation lawsuit is one of the most important means of protecting the legitimacy and the rights and freedoms of individuals and employees in contemporary countries, but despite their great importance, they are not sufficient to fully protect individuals. It occurs frequently in daily applications that a ruling in a cancellation lawsuit executes an administrative decision retroactively to the date of its issuance, which in the event of its implementation constitutes a threat to the rights of third parties, and prejudice to their personal legal positions. Touch their own legal status. The case of a full court is the case that allows the judge not only to examine the legality of the administrative work, and then to cancel or not to cancel that work, or in other words, it does not allow the judge to merely condemn the actions of the state in violation of the law, but rather that goes to correcting and resolving the legal status itself For the appellant, by amending or changing the administrative work, if it is proven of course that it is unlawful or incorrect, and a judgment is also issued for him to compensate for the damages resulting from it. This research deals with the complete lawsuit (compensation lawsuit) in terms of its concept, characteristics, and distinction from the cancellation lawsuit. يساهم القضاء الإداري بدور في غاية من الأهمية في مجال مراقبة مشروعية الأعمال الإدارية وحماية حقوق وحريات الأفراد وهذا من خلال فصله في القضايا المعروضة عليه، ويستمد القضاء الإداري هذه الأهمية من وظيفته الطبيعية كونه الجهاز الرسمي الذي يفرض حكم القانون على جميع الهيئات وأيا كان مركزها وموقعها وطبيعتها كما يفرض حكم القانون على الأفراد وهو مايؤدي في النهاية إلى إقامة دولة القانون ودولة المؤسسات ودولة الحقوق والحريات ولا يمكن تكريس هذه المفاهيم في أرض الواقع دون دور للقضاء الإداري . وتمارس المحاكم الإدارية رقابتها من خلال نوعين من الدعاوى، هما دعوى الإلغاء ودعوى القضاء الكامل. تعد دعوى الإلغاء من أهم وسائل حماية المشروعية وحقوق وحريات الأفراد والموظفين في الدول المعاصرة، ولكن على الرغم من أهميتها الكبيرة إلا أنها لاتكفي لحماية الأفراد حماية كاملة. ويحدث كثيراً في التطبيقات اليومية أن يصدر حكم في دعوى الإلغاء يعدم قراراً إدارياً وبأثر رجعي إلى تاريخ صدوره ما يشكل ولا ريب في حالة تنفيذه تهديداً لحقوق الغير المكتسبة، ومساساً بمراكزهم القانونية الشخصية، وهذا يستتبع بالضرورة وجود قضاء آخر يضمن الحماية الكاملة للأفراد ضد تصرفات الإدارة التي تمس مركزاً قانونيا خاصاً بهم. فدعوى القضاء الكامل هي تلك الدعوى التي تتيح للقاضي ليس فقط مجرد بحث مدى مشروعية العمل الإداري، ومن ثم إلغاء أو عدم إلغاء ذلك العمل، أو بمعنى آخر لا تتيح للقاضي فقط مجرد إدانة أعمال الدولة المخالفة للقانون، وإنما يتجاوز ذلك إلى تصحيح وحسم المركز القانوني الذاتي للطاعن وذلك بتعديل العمل الإداري أو تبديله إذا ثبت بطبيعة الحال عدم مشروعيته أو عدم صحته، والحكم له كذلك بالتعويض عن الأضرار الناجمة عنه. يتناول هذا البحث دعوى القضاء الكامل (دعوى التعويض) من حيث مفهومها، خصائصها، وتمييزها عن دعوى الإلغاء.